Analisa Pengujian Kelayakan PMT 150 kV Bay Mandirancan I Berdasarkan Parameter Breaker Analyzer di Gardu Induk Sunyaragi - Adis Galih Firdaus; Rahmat Hidayat (Teknik Elektro Politeknik Negeri Padang, 2021)
Electricity is an energy that is very important in all aspects of people's life. PT. PLN (Persero) as a provider and supplier of electrical energy in Indonesia, is absolutely required to supply electricity to the community properly. One of the efforts to do this is to ensure the appropriateness and reliability of the equipment used in the electric power transmission system by carrying out routine testing and maintenance. The equipment that plays a vital role in the electric power transmission system is the Circuit Breaker (CB) because it functions as a mechanical switch used to cut off the flow of the load current which plays an important role when a disturbance occurs to protect other equipment from damage. Therefore, the reliability of this CB must always be maintained. In this study, tests were carried out four times on the CB 150 kV Mandirancan I contacts by measuring the synchronization of working time for open, close, reclose, and OCO (Open - Close - Open) contacts using a Breaker Analyzer measuring instrument. The test results show an anomaly in terms of the synchronization of the contacts, where one of the contacts works faster when it closes due to the longer pull of the motor than the other contacts. To overcome this, it is recommended to reset the Motor Run Limit Switch PMT so that the length of time the motor works is similar in all of its contacts.